Beginning AutoCAD 2016 : exercise workbook - Shrock, Cheryl R.; Heather, Steve (Industrial Press, 2015)
Annotation Beginning AutoCAD 2016 Exercise Workbook is the right book for users new to AutoCAD or who want to brush up on the basics. This is a clear, no nonsense, easy-to-follow text that helps user learn AutoCAD quickly and easily. All exercises print easily on a standard 8 " x 11" printer
Issued with a trial version of AutoCAD 2016.
"Created for classroom instruction or self-study tutorial. Totally updated for AutoCAD 2016 or 2016LT"--Cover
Includes index.
Keywords: AutoCAD.; AutoCAD; Computer-aided design.; Computer graphics.; elektronické knihy; electronic books